Business games for management and economics : learning by playing - Bazil, Leon. (Singapore ; London : World Scientific, 2012)
"Business Games for Management and Economics: Learning by Playing presents board and video business games which combine teamwork with individual decisions based on computer models. Business games support integration of learning experience for different levels of education and between different disciplines: economics, management, technological, environmental and social studies. The work is based on experience in adaptation, design and conducting of field, and board and video games played in college settings within standard schedules. Most of the games are played in Modeling and Simulation, Microeconomics, Logistics and Supply Chain Management courses. Game boards are 2- or 3-dimensional displays of subsystems, their components and phases of technological and business processes, which allow customization of games of the same type for different missions in schools, universities, and corporate training centers. The range of games applied to economics and management classes spreads from 2-person games for kid's 'Aquarium' up to the REACTOR games for several teams of executives."--Publisher's website.
Choosing a business game. Learning by playing -- Models for business games -- Field and board games -- Computer games -- Choosing a game -- Designing a business game. The purpose of the game -- The idea of the game -- Business game hardware design -- Software for business games -- Business games for system design.
Includes bibliographical references (p. 353-365) and index.
Keywords: Management games